2015
DOI: 10.1186/s13028-015-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

An international multi-centre prospective study on the efficacy of an intraarticular polyacrylamide hydrogel in horses with osteoarthritis: a 24 months follow-up

Abstract: BackgroundPolyacrylamide hydrogel (PAAG) was evaluated recently to treat osteoarthritis (OA) in horses with highly encouraging results; however no long term field-study was done to explore its clinical efficacy and lasting effect. The objective of this study was to evaluate the efficacy of PAAG in improving clinical signs of OA in horses. We hypothesized that lameness grade would significantly improve and the effect would last at least 2 years in osteoarthritic joints treated with PAAG. Forty three horses olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…Our results indicate that practitioners outside the USA more frequently used polyacrylamide hydrogel than practitioners in the USA. Investigations into the use of polyacrylamide hydrogel have been primarily based out of Europe (31,32), where it has been available on the market for a longer time period than in the USA. These factors indicate that practitioners outside the USA are likely more familiar with the product and have had more opportunities to use this product than practitioners in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that practitioners outside the USA more frequently used polyacrylamide hydrogel than practitioners in the USA. Investigations into the use of polyacrylamide hydrogel have been primarily based out of Europe (31,32), where it has been available on the market for a longer time period than in the USA. These factors indicate that practitioners outside the USA are likely more familiar with the product and have had more opportunities to use this product than practitioners in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic benefits for PAAG have been reported in an observational study in the horse, where one treatment of 2 ml PAAG in fetlock or carpus joints was found to have a significant effect on lameness and effusion during the first month post treatment, after which this effect increased progressively until 6 months, and then stabilized up until 24 months 12 . Recently an observational pilot study of 60 human knees with OA, which were treated with nondegradable PAAG, showed promising results for pain reduction 13 .…”
Section: Discussionmentioning
confidence: 88%
“…Five joints without OA served as controls. The horses were part of a large prospective clinical study carried out at three different equine centers, where 1e4 (mean 2) ml of PAAG had been injected per joint and where the effect of the treatment was followed postoperatively for up to 2 years 12 . Histopathological examination was carried out on leg joints from horses having died during that period.…”
Section: A Study Of Osteoarthritic Joints In the Horsementioning
confidence: 99%
See 1 more Smart Citation
“…E também o hidrogel de poliacrilamida (PAHG), que são frequentemente utilizados e associados com o efeito anti-inflamatório, proteção osteocondral e regeneração, melhora da viscosidade e da mobilidade articular (TNIBAR et al, 2015;FRISBIE et al, 2016;SOUZA, PARETSIS & ZOPPA, 2020).…”
Section: Introductionunclassified